2021
DOI: 10.3390/polym13132074
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Role of π-Interactions in Polyelectrolyte Complexes Using Rationally Designed Peptides

Abstract: Electrostatic interactions, and specifically π-interactions play a significant role in the liquid-liquid phase separation of proteins and formation of membraneless organelles/or biological condensates. Sequence patterning of peptides allows creating protein-like structures and controlling the chemistry and interactions of the mimetic molecules. A library of oppositely charged polypeptides was designed and synthesized to investigate the role of π-interactions on phase separation and secondary structures of poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 77 publications
1
9
0
Order By: Relevance
“…Additionally, MB having three aromatic rings is more hydrophilic than DOX with anthraquinone rings. Moreover, our previous study confirmed that the contribution of electrostatic interactions, pi‐interactions, and hydrophobic forces drive MB encapsulation within the complex phase, where higher charge density sequence pairs with phenylalanine, p(kKf)+p(eEf), showed almost complete encapsulation [45] . Here, the most hydrophobic sequence pair with highest charge density, p(kKl)+p(eEl), had the highest encapsulation efficiency and highest retention within the complex phase.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…Additionally, MB having three aromatic rings is more hydrophilic than DOX with anthraquinone rings. Moreover, our previous study confirmed that the contribution of electrostatic interactions, pi‐interactions, and hydrophobic forces drive MB encapsulation within the complex phase, where higher charge density sequence pairs with phenylalanine, p(kKf)+p(eEf), showed almost complete encapsulation [45] . Here, the most hydrophobic sequence pair with highest charge density, p(kKl)+p(eEl), had the highest encapsulation efficiency and highest retention within the complex phase.…”
Section: Discussionsupporting
confidence: 65%
“…Moreover, our previous study confirmed that the contribution of electrostatic interactions, pi-interactions, and hydrophobic forces drive MB encapsulation within the complex phase, where higher charge density sequence pairs with phenylalanine, p(kKf) + p(eEf), showed almost complete encapsulation. [45] Here, the most hydrophobic sequence pair with highest charge density, p(kKl) + p(eEl), had the highest encapsulation efficiency and highest retention within the complex phase. Optical microscopy and deconvolution of the FTIR spectra showed that DOX does not affect the phase behavior of complexes, while MB induces hydrogen bonding in p(kKl) + p(eEl), causing a transition from liquid coacervates to solid precipitates.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Figure S2 suppressed at concentration values higher than this critical concentration. Leon et al demonstrated that hydrophobic interactions were dominant for phenylalanine aggregation at high salt concentrations (> 250 mM), while π-interactions and electrostatic interactions such as charge-charge interactions played an important role in the aggregation at low salt concentrations (≤ 250 mM) [44]. These previous reports indicated that polymer aggregation occurs at a critical concentration of the solution, which is proposed to be C NaCl = 150 mM for the J-aggregation of TPPS in the present study.…”
Section: J-aggregation Of Tpps In the Dilute Solutionmentioning
confidence: 99%